Studi Pemberdayaan Masyarakat Pedesaan Melalui Teknologi Informasi Dan Komunikasi - Popi Andiyansari (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2014)
Under the provisions of the Universal Service Obligation (USO) on the provision of facilities and access to ICT, Menkominfo pioneering Village Program information in which there is a program called Pusat Layanan Internet Kecamatan (PLIK). However, this program only to dwell on the form of the means of access services and ICT infrastructure alone. Whereas people in the border areas, rural, and remote mostly unable to use ICT and the internet. This is an opportunity PLIK Nanggulan 2 to conduct training, socialization, and community empowerment through ICT. Formulation of the problem in this study describes How Rural Community Empowerment Through Information and Communication Technology Pusat Layanan Internet Kecamatan in PLIK Nanggulan 2 Kulon Progo Yogyakarta. This study used a qualitative research methodology with case study method. Results from this study that the digital divide in rural communities are not only related to the lack of access and means of course, but also gaps in the ability to use ICT. In this case PLIK Nanggulan 2 perform three steps of empowerment, among others: technical training, socialization ethical use of the internet, planting motivation to seek information via the internet. Empowered communities through ICT with models 'second hand'. People in the region have understood the function Nanggulan internet but not able to independently use the internet, then delegate the functions of the Internet to others who understand. In this regard, research advice to PLIK Nanggulan 2 in order to improve the quantity and quality of the organization and consistency of community empowerment. Keywords: Community Empowerment, PLIK Nanggulan 2, ICT, Information Village ABSTRAK Penelitian ini dilakukan pada program Pusat Layanan Internet Kecamatan (PLIK) Nanggulan 2 Kulon Progo Yogyakarta. Penelitian ini menjelaskan tentang Bagaimanakah Pemberdayaan Masyarakat Pedesaan Melalui Teknologi Informasi dan Komunikasi pada Program Pusat Layanan Internet Kecamatan di PLIK Nanggulan 2 Kulon Progo Yogyakarta. Penelitian ini menggunakan metodologi penelitian kualitatif dengan metode penelitian studi kasus. Hasil dari penelitian ini bahwa kesenjangan digital pada masyarakat pedesaan tidak hanya terkait dengan minimnya akses dan sarana saja, akan tetapi juga kesenjangan secara kemampuan dalam menggunakan TIK. Dalam hal ini PLIK Nanggulan 2 melakukan tiga langkah pemberdayaan, antara lain: pelatihan secara teknis, sosialisasi etika penggunaan internet, penanaman motivasi untuk mencari informasi melalui internet. Masyarakat terberdayakan melalui TIK dengan model ‘tangan kedua’. Masyarakat di wilayah Nanggulan telah memahami fungsi internet akan tetapi tidak mampu secara mandiri menggunakan internet, kemudian mendelegasikan fungsi internet kepada pihak lain yang lebih memahami. Dalam hal ini, saran penelitian untuk PLIK Nanggulan 2 agar meningkatkan kuantitas dan kualitas organisasi dan konssitensi pemberdayaan masyarakat. Kata Kunci : Pemberdayaan masyarakat, PLIK Nanggulan 2, TIK, Desa informasi